An Employee’s Living Wage and Their Quality of Work Life: How Important Are Household Size and Household Income? - Carr, S; Haar, J; Hodgetts, D; Arrowsmith, J; Parker, J; Young-Hauser, A; Alefaio-Tuglia, S; Jones, H (Hapres, 2019)
Living Wage (LW) campaigns normally assume a prototype household configuration in setting their LW rate, comprised of number of dependent householders and the number of incomes. This information is used to calculate the hourly pay rate required to sustain their quality of life and work life. Real households are nonetheless diverse in terms of number of householders and incomes, rendering the living wage conceptually more of a continuous variable than a single constant, across a wage spectrum. We explored this spectrum and its links to job attitudes with a nationally representative sample of N = 1011 low-waged New Zealanders. We measured each participant’s: hourly pay rate, number of household dependents and total household income, alongside individual job attitudes indicative of quality of work life (job satisfaction, work engagement, career satisfaction, meaningful empowerment, affective commitment, organizational citizenship behaviours and work-life balance). As a set, job attitudes consistently pivoted upwards into positive values approximating the campaign LW rate in New Zealand, regardless of either number of household dependents or household income (net of personal wage). However household income net of personal wage (unlike number of household dependents) buffered the gradient of the pivot upwards. The gradient was steeper (more clearly transformational and binary) among lowest-waged workers, in single-income households. To the extent that job attitudes as a set are already widely linked to individual and unit-level productivity, paying at or above the living wage threshold may bring productivity gains and thereby contribute toward decent work and economic development combined.
Keywords: Living wage; Working poverty; New Zealand; Decent work; Job attitudes